PENGARUH UPAH DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DALAM PERSPEKTIF EKONOMI ISLAM PADA PT. REZEKI SURYA GASINDO - Rahul Rivaldo; Anzu Elvia Zahara (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to analyze the effect of wages and work environment on employee performance at PT. Rezeki Surya Gasindo. The background of this research is based on the importance of decent wages and a conducive work environment as factors that can enhance employee productivity and work quality. This study employs a quantitative method with a causal associative approach. Data were obtained through the distribution of questionnaires to all employees of PT. Rezeki Surya Gasindo and measured using a Likert scale. The data analysis techniques used in this study include validity and reliability tests, R-square test, and hypothesis testing through bootstrapping with SmartPLS 3 software. The results indicate that wages have a positive and significant effect on employee performance, and similarly, the work environment also has a positive and significant effect on employee performance. Simultaneously, wages and work environment are proven to have a significant effect on employee performance. These findings suggest that the company should pay attention to providing appropriate wages and creating a comfortable work environment in order to optimize employee performance.